Comparing Visual Search Behavior among the Expert and Near-Expert Players in Basketball Jump Shots; An Ex Post Facto Study - Samira Moeinirad; Behrouz Abdoli; Alireza Farsi; Nasoor Ahmadi (Vesnu Publications, 2018)
Introduction: One of the subcategories of studies about expertise is the study of visual skills involved in the performance of the expertise. Many researchers have tried to offer different solutions by comparing these skills among expert and near-expert players. The current study aimed to compare visual search behavior in skilled and near-skilled players at basketball jump shot. Materials and Methods: The participants were basketball players who were divided to skilled and near-skilled ones based on the years of playing and the league they play in. To record and collect research data, sensomotoric instruments (SMI) eye tracking glasses with 60 Hz sample rate were used. All participants performed some jump shot and data related with gaze behavior (number of fixations and fixation duration) were collected and compared using independent t test. Results: There was a significant different in number of fixations (P = 0.040) and no significant different in fixation duration between skilled and near-skilled participants. Conclusion: Based on the results of this study, it concluded that gaze behavior can be one of the distinguishing factors of different skill levels, which focus on it can help to improve the expertise performance in sport by identifying more important and effective factors in training.